2023
DOI: 10.1021/acs.chemrev.3c00033
|View full text |Cite
|
Sign up to set email alerts
|

Plate-Like Colloidal Metal Nanoparticles

Abstract: The pseudo-two-dimensional (2D) morphology of plate-like metal nanoparticles makes them one of the most anisotropic, mechanistically understood, and tunable structures available. Although well-known for their superior plasmonic properties, recent progress in the 2D growth of various other materials has led to an increasingly diverse family of plate-like metal nanoparticles, giving rise to numerous appealing properties and applications. In this review, we summarize recent progress on the solution-phase growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 532 publications
0
27
0
Order By: Relevance
“…In the growth solution, as with seed synthesis, the selected reductant, pH, surfactant, halides, solvent, and silver salts all act to promote growth along specific crystal facets . Undoubtedly, there are many “handles” for controlling shape-directed growth; comprehensive reviews of each of these aspects are available elsewhere. ,, …”
Section: From Colloidal Synthesis To In Situ Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In the growth solution, as with seed synthesis, the selected reductant, pH, surfactant, halides, solvent, and silver salts all act to promote growth along specific crystal facets . Undoubtedly, there are many “handles” for controlling shape-directed growth; comprehensive reviews of each of these aspects are available elsewhere. ,, …”
Section: From Colloidal Synthesis To In Situ Growthmentioning
confidence: 99%
“…24 Undoubtedly, there are many "handles" for controlling shapedirected growth; comprehensive reviews of each of these aspects are available elsewhere. [21][22][23][24]140,159 In addition, colloidal satellite structures or systems studying the growth of nanoparticles on another host nanomaterial, such as nanoparticle-decorated nanoplatelets, nanotubes, or other colloidal supports, offer interesting possibilities for generating hybrid structures, which we discuss further in Section 2.2. 52,160−163 Furthermore, the translation of the synthetic rules from this literature, especially regarding the promotion of nucleation on the colloidal support, could be informative for further developing synthetic protocols whereby gold nanoparticles are grown on substrates.…”
Section: Seed-mediated Growthmentioning
confidence: 99%
“…Statistical analysis of the micrographs showed that the diameter of particles is 20–25 nm and the thickness is 5–10 nm. This allows us to classify them as nanoplates …”
Section: Resultsmentioning
confidence: 99%
“…Shape-controlled synthesis of metal nanocrystals offers a pathway to regulate their optical, catalytic, and biological properties. This approach typically involves the use of capping agents, which selectively bind to specific facets to influence the atomic deposition rate or surface energy, thereby yielding nanocrystals with different aspect ratios or bounded by distinct facets. The unique ability of capping agents to drive anisotropic growth makes a deep understanding of their roles essential for synthesizing metal nanomaterials with the desired shapes and properties. Often, these roles are inferred from the shape of the product synthesized.…”
Section: Introductionmentioning
confidence: 99%